Investigation of isomerization of dexibuprofen in a ball mill using chiral capillary electrophoresis. Issue 17 (27th January 2021) - Urlaub, Jonas; Kaiser, Reinhard P.; Scherf‐Clavel, Oliver; Bolm, Carsten; Holzgrabe, Ulrike
Abstract: Besides the racemate, the S ‐enantiomer of ibuprofen (Ibu) is used for the treatment of inflammation and pain. Since the configurational stability of S ‐Ibu in solid state is of interest, it was studied by means of ball milling experiments. For the evaluation of the enantiomeric composition, a chiral CE method was developed and validated according to the ICH guideline Q2(R1). The addition of Mg 2+, Ca 2+, or Zn 2+ ions to the background electrolyte (BGE) was found to improve Ibu enantioresolution. Chiral separation of Ibu enantiomers was achieved on a 60.2 cm (50.0 cm effective length) x 75 μm fused‐silica capillary using a background electrolyte (BGE) composed of 50 mM sodium acetate, 10 mM magnesium acetate tetrahydrate, and 35 mM heptakis‐(2, 3, 6‐tri‐O‐methyl)‐β‐cyclodextrin (TM‐β‐CD) as chiral selector. The quantification of R ‐Ibu in the mixture was performed using the normalization procedure. Linearity was evaluated in the range of 0.68–5.49% R ‐Ibu (R 2 = 0.999), recovery was found to range between 97 and 103%, the RSD of intra‐ and interday precision below 2.5%, and the limit of quantification for R ‐ in S ‐Ibu was calculated to be 0.21% (extrapolated) and 0.15% (dilution of racemic ibuprofen), respectively. Isomerization of S ‐Ibu was observed under basic conditions by applying long milling times and high milling frequencies.